Behavioral effects of manganese injected in the rat substantia nigra are potentiated by dicumarol, a DT-diaphorase inhibitor. - Díaz-Véliz, G; Mora, S; Gómez, P; Dossi, M; Montiel, J; Arriagada, C; Aboitiz, F; Segura-Aguilar, J (2004)
The purpose of this study was to evaluate the contribution of DT-diaphorase inhibition to in vivo neurodegenerative effects of dopamine (DA) oxidation to the corresponding o-quinones. The neurotoxicity to nigrostriatal DA neurons was induced by injection of manganese pyrophosphate (Mn(3+)) complex as a prooxidizing agent alone or together with the DT-diaphorase inhibitor dicumarol into the right rat substantia nigra. The behavioral effects were compared with those induced after selective lesions of dopaminergic neurons with 6-hydroxydopamine (6-OHDA). Intranigral injection of Mn(3+) and Mn(3+) plus dicumarol produced significant impairment in motor behavior compared with control animals. However, the effect seen in the Mn(3+) plus dicumarol injected group was significantly more severe than that observed in the Mn(3+) alone injected group. In motor activity and rearing behavior, the simultaneous injection of Mn(3+) plus dicumarol produced a 6-OHDA-like impairment. Similar effects were observed in the acquisition of a conditioned avoidance response (CAR). Dicumarol significantly impaired avoidance conditioning although without affecting the motor behavior. The behavioral effects were correlated to the extent of striatal tyrosine hydroxylase (TH)-positive fiber loss. Rats receiving unilateral intranigral Mn(3+) and Mn(3+) plus dicumarol injections exhibited a significant reduction in nigrostriatal TH-positive fiber density in medial forebrain bundle compared with the contralateral noninjected side. In conclusion, this study provides evidence that the neurotoxicity of Mn(3+) in vivo is potentiated by DT-diaphorase inhibition, suggesting that this enzyme could play a neuroprotective role in the nigrostriatal DA systems.